Comparison of the diagnostic accuracy of cell block with cytology smear in serous effusions (Journal of Pathology of Nepal, 2013)
Background: Differentiation between benign and malignant serous effusions always poses a great diagnostic dilemma. Differentiation often requires clinical findings, morphological evaluation and sometimes immunocytochemistry. Diagnostic possibility is enhanced if cell blocks are made along with the conventional cytology smears. This will help the clinicians in both treating the patient and determining the outcome of the disease process. Materials and methods: This hospital-based cross sectional analytical study was carried out in Department of Pathology in National Academy of Medical Sciences, Bir Hospital for one year. The objective of this study was to compare the smears cytology with cell blocks sections in serous effusions. Results: The four criteria scored for each technique were volume of background blood, amount of diagnostic cellular material, degree of cellular degeneration and trauma and architectural preservation. Background blood, amount of diagnostic material present and retention of architecture was more in cell block sections compared with smears cytology; whereas cellular degeneration and trauma was less appreciated in cell block sections which scored more than the smears cytology. Conclusion: Cell block preparation is simple, rapid and inexpensive technique for serous fluids in which malignant cells can be reliably detected thus avoiding unnecessary invasive procedure in patient management. DOI: http://dx.doi.org/10.3126/jpn.v3i6.8998 Journal of Pathology of Nepal (2013) Vol. 3, 482-486